MEDTHINKER: Novel computer‐based simulation to assess technical and nontechnical skills using medical content in healthcare providers. Issue 12 (9th December 2021) - Krishnamurthy, Satish; MacNaughton, Piers; Chin, Lawrence; Dewan, Mantosh
Abstract: The practice of medicine involves an interplay of technical knowledge and skills as well as nontechnical skills. Nontechnical skills include situational awareness, decision making, communication and performance under stress. Both technical skills and nontechnical skills are equally important, and we present a novel simulation MEDTHINKER which has specific medical content as well as measures of nontechnical skills, with specific algorithms and metrics designed to capture core competencies of healthcare performance. 100 residents from three disciplines across four institutions in the US participated in the MEDTHINKER simulation exercise. Pearson correlation coefficients were calculated for the raw scores on the MEDTHINKER simulation. Generalized linear models were used to compare self‐reported satisfaction and overall sense of achievement with normalized scores on the MEDTHINKER simulations. The results demonstrate that productivity and safety had strong positive correlations with ability to adapt, capacity to task focus and good communication skills. Increased overall productivity resulted in a negative correlation with errors rates. Self‐reported job satisfaction and achievement showed strongly positive correlations with each other. Interestingly, adaptability was strongly correlated with productivity and job satisfaction which has many components of workplace well‐being as measured in this research. The data obtained provides validation for the utility of MEDTHINKER which has the ability to assess both technical and nontechnical skills. The data demonstrates that MEDTHINKER can measure indicators of good clinical performance that correlate with self‐reported job satisfaction and achievement.